Professional Tax Consultant Support for Taxpayer Compliance Optimization - Iswandi Iswandi; Sujoko Sujoko (PT. Hafasy Dwi Nawasena, 2025)
Taxpayer compliance is a critical component in sustaining national revenue, particularly within increasingly complex and digitalized tax systems. This study analyzes the role and professional support of tax consultants in optimizing taxpayer compliance in Indonesia. A Systematic Literature Review (SLR) was employed, involving identification, screening, eligibility assessment, and thematic analysis of 22 relevant academic publications. The findings indicate that tax consultants play a strategic role in strengthening both formal and substantive compliance through educational, administrative, and advocacy functions, including assistance with taxpayers’ digital adaptation. However, the review also reveals the ambivalent nature of tax consultants' roles, particularly when service orientation promotes aggressive tax planning that may weaken substantive compliance. Optimizing consultant support requires stronger professional regulation, enhanced digital competencies, technological integration, and collaborative governance between practitioners and tax authorities. This study concludes that tax consultants can serve as strategic partners in improving taxpayer compliance, provided that regulatory frameworks, ethical standards, and compliance ecosystems are systematically reinforced.